The Role of Dexmedetomidine in Pediatric Patients Presenting with an Anticholinergic Toxidrome - Mitchell Zekhtser; Erin Carroll; Molly Boyd; Shashikanth Ambati (Case Reports in Critical Care)
Background. We report two pediatric cases of anticholinergic toxidrome, including the youngest reported to date, in which standard therapeutic strategies were either contraindicated or ineffective, while treatment with dexmedetomidine was rapidly efficacious with no adverse effects. Moreover, with the recent shortage of physostigmine, we highlight an alternative treatment in this clinical setting. Case Summaries. In case 1, a two-year-old had an overdose presenting with an anticholinergic toxidrome. However, his hypopnea precluded the use of benzodiazepines due to the high likelihood of intubation. In case 2, a 14-year-old had a polypharmacy overdose inducing agitated delirium that was refractory to high-dose benzodiazepines. Due to the unknown ingestion, physostigmine was avoided. In both cases, dexmedetomidine helped the patient remain calm and metabolize the ingestions. Conclusion. Our experience suggests that dexmedetomidine may be a useful adjunct in anticholinergic presentations in the setting of polypharmacy, when standard therapy is proven ineffective, contraindicated, or unavailable.